Chinese leadership: Provincial perspectives on promotion and performance. (June 2019) - Sun, Jiajing; Cole, Michael; Huang, Zhiyuan; Wang, Shouyang
This article addresses whether the promotion of China's provincial leadership can be explained through economic growth or alternative factors (experience, education or having previously held a central government post). We use promotion definitions, based on official administrative rankings and a more accurate reflection of political-governmental power relationships, and five econometric models. Analysis is also located within specific scholarship about promotion in the Chinese bureaucracy, bureaucratic cultures and transitions from socialism. Findings suggested some support for the idea that economic growth records affected promotion in terms of the second definition and additional evidence to imply impacts from non-economic factors.